2000
DOI: 10.1021/la991074v
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Temperature of Poly(tert-butyl methacrylate) Langmuir−Blodgett Film and Spin-Coated Film by X-ray Reflectivity and Ellipsometry

Abstract: The glass transition temperature (Tg) of poly(tert-butyl methacrylate) (PtBMA) Langmuir-Blodgett (LB) films relative to that of spin-coated films on a silicon substrate is investigated by ellipsometry and X-ray reflectivity. The Tg of spin-coated films on an oxide-free silicon wafer decreases as the film thickness decreases, which is consistent with the majority of the previous reports in the literature. However, the transition temperature of the LB films is nearly independent of the total thickness, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 27 publications
3
57
1
Order By: Relevance
“…It is regarded that the dead layer in the three-layer model has almost no mobility [22]. Therefore, the shift of T g is contributed both by surface layer ( T sur f g) and bulk layer ( T bulk g), in which the surface layer is thought as a region of enhanced mobility [28, 29]. Polymer chain ends at the air-polymer interface tends to move toward the surface, which leads to the increase of free volume and acceleration of chain mobility [30].…”
Section: Resultsmentioning
confidence: 99%
“…It is regarded that the dead layer in the three-layer model has almost no mobility [22]. Therefore, the shift of T g is contributed both by surface layer ( T sur f g) and bulk layer ( T bulk g), in which the surface layer is thought as a region of enhanced mobility [28, 29]. Polymer chain ends at the air-polymer interface tends to move toward the surface, which leads to the increase of free volume and acceleration of chain mobility [30].…”
Section: Resultsmentioning
confidence: 99%
“…Polymers with the butyl methacrylate group have been particularly of interest, because the glass transition temperature of butyl methacrylate (PBMA) is relatively lower than that of methacrylate (PMMA) polymers [12,13]. Due to its transparency and easy processability, PBMA can be used as a polymer matrix for synthesis of different nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, See et al reported similar T g dependencies determined from X-ray reflectometry (XR) measurements for LBK multilayers made from poly(tert-butyl methacrylate) and the corresponding spincoat samples. [5] Mabuchi et al determined via energy-transfer measurements the onset temperature for chain relaxation in LBK films made from poly(vinylalkanal acetal) to be close to the T g of the bulk material. [6] In the following, a detailed study of LBK multilayers made from poly(ethyl methacrylate) PEMA is reported.…”
Section: Introductionmentioning
confidence: 96%